Marginalisations and Redefinitions of Kinship in Contemporary Cuba - Härkönen, Heidi (feminists@law, 2023)
This article examines the marginalisations and redefinitions taking place in kinship relations and the resources that persons in a precarious social position draw on to cope with exclusions in the context of large-scale social, legal, political, and economic change. In situations of global and local transformation, people may become marginalised in their social relations for various reasons, but in the margins, they can also find resources to alleviate or redefine such experiences. Such processes are complexly shaped by intersectional differences and inequalities of gender, sexuality, race, and age. Drawing on long-term ethnographic research in Cuba, a country that is currently undergoing extensive structural changes, this article focuses on the marginalisations of kinship through the ethnographic story of an elderly woman and her kin encountering unexpected exclusions in their relationships. As Cuba transforms from a socialist, egalitarian society into a new social order increasingly guided by the privileges of money, social relations are redefined in terms of shifts in understandings of marginality. In the margins, we find new arrangements of both discrimination and support, but the political potential of such processes is ambiguous and culturally and historically contingent.